Experiences of Hemodialized Patients WHO Have Recovered From Covid-19 In Medan City - Narwastu Telaumbanua, Hariesty Talenta (Devotion : Journal of Research and Community Service, 2022)
Hemodialysis is one of the appropriate treatments for patients with ESRD. The glomerular filtration rate in the kidneys decreased to <60 mL/min and the creatinine and albumin values ​​in the patient's urine increased to >30 mg/g, so that patients with chronic kidney failure had to undergo a treatment to balance and replace the work of the kidneys, namely the hemodialysis process. The research design used in this study is a descriptive phenomenological design. Phenomenology is a method that seeks to find the essence and meaning of phenomena as they are experienced, especially through in-depth interviews with people who have had relevant experiences. In this study, the characteristics of participants were obtained based on the demographic data obtained, where the average age of hemodialysis participants who were positively exposed to COVID-19 was more likely to be under 50 years old, with 7 participants, and 4 participants over 50 years old. . The gender of hemodialysis participants in this study was found to be 6 men and 5 women. Another characteristic that was obtained was that the ethnic groups that participated in this study were, the Batak tribe numbered 6 people, Karo 1 person, Malay 1 person, Padang 1 person and Javanese 1 person. The religion of the participants in this study, it was found that 2 Protestant Christians, 8 Muslims, and 1 Catholic Christian